MONITORING EFEK SAMPING OBAT ANTITUBERKULOSIS FASE INTENSIF DAN LANJUTAN PASIEN DEWASA TUBERKULOSIS DI RSUD KOTA BANDUNG - Siti Thannisa Aisyah Gumanti (2020)
Tuberculosis is an infectious disease caused by the Mycobacterium tuberculosis bacteria that can be transmitted through a splash of phlegm. The use of antituberculosis drugs can lead to a wide range of side effects depending on the length of treatment TB. Based on TB treatment conditions that have a long drug intake duration as well as many types of medications, there will be a high risk of side effects or toxicity. The purpose of this research is to figure out the adverse effects that arise in intensive and advanced phase patients, knowing there are differences in the side effects that arise in relapse patients, knowing the incidence rate of the drug side effects of TB in RSUD Kota Bandung, knowing the highest prevalence that causes the incidence of adverse reactions during TB treatment. This method of research authors uses a descriptive observational method with a cross sectional approach. Sampling techniques using purposive sampling are based on inclusion criteria with a minimum sample of 34. The results of comparative test, obtained P-value of 0.549 > 0.05, indicating that there is no meaningful (significant) difference between the side effects of the drug arising in new patients with relapse patients.